Antibiotic-taking experiences of undergraduate college students. - Aronson, Barbara S (Journal of the American Academy of Nurse Practitioners, 2006)
Purpose: The purpose of this qualitative descriptive study was to explore the medication-taking experiences of undergraduate college students prescribed short-term antibiotic therapies and to describe factors influencing their adherence. Data sources: Thirty-four undergraduate students prescribed antibiotics for treatment of an acute infectious illness at a large university health center were recruited to participate in this study. Semistructured telephone interviews were conducted after students finished their course of treatment. Qualitative descriptive content analysis was used to analyze the transcripts typed from the audio-taped phone interviews. Conclusions: The main theme that emerged from the data was antibiotic-taking self-management. Most participants were able to adapt medication regimens into their daily routines, and used events in their day and specific reminder strategies to help them to remember to take their medications. This occurred despite an ever-changing class and work schedule and being prescribed complex, lengthy antibiotic regimens. Most dosing errors occurred during times when schedules changed or students were off campus during weekends or college breaks. A small number of students discontinued therapy early because of side effects or forgetfulness. Implications for practice: By understanding factors that influence antibiotic adherence from a college student perspective, healthcare providers can suggest strategies to promote adherence that are tailored to the specific needs of this unique population. © 2006 American Academy of Nurse Practitioners.
Keywords: *Anti-Bacterial Agents/tu [Therapeutic Use]; *Patient Compliance; *Self Care; *Students; Adolescent; Adult; Anti-Bacterial Agents; Antibiotic adherence; College students; Female; Humans; Male; Medication self-management; Patient Compliance; Self Care; Students; United States; adolescent; adult; antiinfective agent; article; dept.nur; female; human; male; patient compliance; self care; student

Care of the adult patient with cystic fibrosis. - Aronson, Barbara S; Marquis, Melissa (Medsurg nursing : official journal of the Academy of Medical-Surgical Nurses, 2004)
Recently published consensus statements and conference proceedings from the Cystic Fibrosis Foundation provide new direction with regard to the etiology, diagnosis, and treatment of the adult patient with cystic fibrosis (CF). Survival has improved through early diagnosis and improved treatment, and aggressive management of complications. The current state of knowledge, the most recent evidence-based treatment options, and essentials of nursing care for the adult patient with CF are outlined.
Keywords: *Cystic Fibrosis/th [Therapy]; Adult; Age Factors; Cystic Fibrosis; Cystic Fibrosis/di [Diagnosis]; Cystic Fibrosis/ep [Epidemiology]; Cystic Fibrosis/et [Etiology]; Diabetes Mellitus; Diabetes Mellitus/et [Etiology]; Diabetes Mellitus/pc [Prevention & Control]; Female; Gastrointestinal Diseases; Gastrointestinal Diseases/et [Etiology]; Gastrointestinal Diseases/pc [Prevention & Control]; Genetic Predisposition to Disease; Genetic Predisposition to Disease/ge [Genetics]; Humans; Infection Control; Infection Control/mt [Methods]; Longevity; Nurse's Role; Phenotype; Reproductive Medicine; Reproductive Medicine/mt [Methods]; Respiratory Therapy; Respiratory Therapy/mt [Methods]; Respiratory Tract Infections; Respiratory Tract Infections/et [Etiology]; Respiratory Tract Infections/pc [Prevention & Control]; Terminal Care; Terminal Care/mt [Methods]; adult; age; artificial ventilation; case report; cystic fibrosis; dept.nur; diabetes mellitus; female; gastrointestinal disease; genetic predisposition; genetics; human; infection control; longevity; methodology; nurse attitude; phenotype; reproduction; respiratory tract infection; review; terminal care; ⛔ No DOI found

Enhancing evidence bases for interventions in a baccalaureate program. - Aronson, Barbara S; Rebeschi, Lisa M; Killion, Susan Westrick (Nursing education perspectives, 2007)
Modifying the sequence, objectives, and research-based content for a nursing interventions course in a baccalaureate curriculum resulted in improved outcomes including enhancement of the evidence bases for nursing interventions. A mixed methods research study demonstrated better student preparation for clinical experiences and improved satisfaction with course content, consistency, and sequencing. Faculty reported improved integration of theory, research, and practice. Although grades were slightly lower in the new course, the positive outcomes greatly outweighed this expected finding. A foundation for improving the evidence bases for future nursing practice is guided by the curricular modifications described in this article.
Keywords: *Attitude of Health Personnel; *Curriculum; *Education, Nursing, Baccalaureate/og [Organization & Administration]; *Evidence-Based Medicine/ed [Education]; *Nursing Research/ed [Education]; *Students, Nursing/px [Psychology]; Attitude of Health Personnel; Clinical Competence; Connecticut; Curricular and course development; Curriculum; Curriculum/st [Standards]; Diffusion of Innovation; Education, Nursing, Baccalaureate; Evidence-Based Medicine; Evidence-based interventions; Faculty, Nursing; Focus Groups; Health Knowledge, Attitudes, Practice; Health Services Needs and Demand; Humans; Nursing Education Research; Nursing Methodology Research; Nursing Research; Organizational Objectives; Program Evaluation; Qualitative Research; Questionnaires; Skills laboratory; Student learning outcomes; Students, Nursing; Surveys and Questionnaires; United States; article; attitude to health; clinical competence; curriculum; dept.nur; education; evaluation; evidence based medicine; health care quality; health personnel attitude; health service; human; information processing; mass communication; nursing education; nursing methodology research; nursing research; nursing student; organization; organization and management; peer-reviewed; psychological aspect; qualitative research; questionnaire; standard; ⛔ No DOI found

Technology use and technological self-efficacy among undergraduate nursing faculty - Roney, Linda N.; Westrick, Susan J.; Acri, Mary C.; Aronson, Barbara S.; Rebeschi, Lisa M. (Nursing Education Perspectives (Wolters Kluwer Health), 2017)
AIM This study explored faculty responses to a survey about using technology to teach undergraduate nursing students. BACKGROUND Little is known regarding faculty confidence, technology use, or supports for integrating technology into nursing education. METHOD A descriptive correlational design was utilized to explore the relationship between technology use and technological self-efficacy in faculty (N = 272) who teach at Commission on Collegiate Nursing Education--accredited nursing programs. Instruments used were a sociodemographic questionnaire, the Roney Technology Use Scale, and the Technology Self-Efficacy Scale. RESULTS Participants who taught didactic content had moderate technology use as compared to those teaching didactic and clinical/laboratory who reported high levels of technology use. A weak relationship between age and technological self-efficacy (ρ =.127, p < .05) was also found. CONLUSION This research was an initial step in understanding levels of technology use and responses to this challenge by undergraduate nursing faculty.
Keywords: Adult; Bivariate Statistics; Coefficient Alpha; Computer Assisted Instruction; Computer Literacy; Confidence; Confidence Intervals; Content Validity; Correlational Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Education Research; Education, Nursing, Baccalaureate; Educational Status; Educational Technology -- Utilization; Faculty Development; Faculty Practice; Faculty, Nursing; Female; Human; Male; Middle Age; Nonexperimental Studies; Nurse Faculty; Nursing Education; P-Value; Promotion and Tenure; Questionnaires; Scales; Schools, Nursing; Self-Efficacy; Socioeconomic Factors; Students, Nursing, Baccalaureate; Summated Rating Scaling; Surveys; T-Tests; Teaching Methods; Technological Self-Efficacy; Technology; adult; age; article; clinical laboratory; controlled study; dept.nur; dept.swk; female; human; human experiment; major clinical study; male; nursing education; nursing student; peer-reviewed; questionnaire; self concept; teaching